PENGARUH STRATEGIC LEADERSHIP PADA ORGANIZATIONAL LEARNING MELALUI ACCOUNTING INFORMATION SYSTEM PADA PERUSAHAAN NON MANUFAKTUR DI SURABAYA - Yessica M Halim; Josua Tarigan (Business Accounting Review, 2016)
The purpose of this research was to identify the influence of Strategic Leadership Toward Organizational Learning with Accounting Information System as the mediating variable of Non Manufacturing Firms in Surabaya. The variables were: Strategic Leadership, Organization Learning, and Accounting Information System. The number of samples were 95 respondents. The data analysis technique used was Partial Least Square. The data then analyzed by SmartPLS software application.  This research showed that Strategic Leadership positively influenced toward Organization Learning; Strategic Leadership positively influenced toward Accounting Information System, but there was no influence of Accounting Information System on Organization Learning.